Measuring Top Incomes Using Tax Record Data: A Cautionary Tale from Australia - Burkhauser, R.V.; Burkhauser, Richard V.; Wilkins, R; Hahn, M; Wilkins, Roger (My University, 2013)
Atkinson, Piketty, and Saez (2011) survey an important new literature using income taxbased data to measure the share of income held by top income groups. But changes in tax legislation that expand the tax base to include income sources (e.g. capital gains, dividends, etc.) disproportionately held by these groups will conflate such an expansion with an increase in the share of income they hold. We provide a cautionary tale from Australia of how comprehensive tax reform legislation in 1985 substantially altered Australian top income series, especially those that do not separate taxable realized capital gains from other taxable income.
Melbourne Institute Working Paper Series
Melbourne Institute Working Paper Series
Keywords: Income & Finance; Income & Finance -- Taxation; Income & Finance -- Income inequality; Income, wealth and finances; Income & Finance; Taxation; Income inequality; Income, wealth and finances